Toward pharmacogenetic SLCO1B1‐guided dosing of methotrexate in arthritis using a murine Slco1b2 knockout model - Zachary L. Taylor (Wiley, 2021)
Abstract Low‐dose methotrexate (MTX) is a first‐line therapy for the treatment of arthritis. However, there is considerable interindividual variability in MTX exposure following standard dosing. Polymorphisms in SLCO1B1 significantly effect MTX clearance, altering therapeutic response. One decreased function variant, rs4149056 (c.521T>C, Val174Ala), slows MTX clearance and in vitro uptake of MTX. This phenotype was recapitulated in a mouse model using a knockout (KO) of the murine orthologue, Slco1b2. Our objective was to investigate the impact of this phenotype on the pharmacokinetics and therapeutic outcomes of low‐dose MTX in a murine model of collagen‐induced arthritis (CIA). We evaluated response to MTX in mice with CIA using wildtype (WT), heterozygous, and KO Slco1b2 mice on a DBA1/J background. Arthritis was macroscopically evaluated daily to quantify disease progression. Mice received 2 mg/kg or a pharmacogenetically guided MTX dose subcutaneously 3 times a week for 2 weeks. MTX concentrations were collected at the end of the study and exposure (day*µM) was estimated using a two‐compartment model. Mice displayed a seven‐fold range in MTX exposure and revealed a significant exposure‐response relationship (p = 0.0027). KO mice receiving the 2 mg/kg dosing regimen had 2.3‐fold greater exposure to MTX (p < 0.0001) and a 66% reduction in overall disease progression (p = 0.011) compared to WT mice. However, exposure and response were equivalent when pharmacogenetically guided dosing was used. These studies demonstrate that an exposure‐response relationship exists for MTX and that Slco1b2 genotype affects MTX exposure and therapeutic response. Such evidence supports the use of SLCO1B1‐pharmacogenetic dosing of low‐dose MTX for patients with arthritis.